2019
DOI: 10.3889/oamjms.2019.168
|View full text |Cite
|
Sign up to set email alerts
|

Association between Glycated Hemoglobin with the Levels of Serum Proinflammatory Cytokines and Antioxidants in Patients with Type 2 Diabetes Mellitus in Universitas Sumatera Utara Hospital

Abstract: BACKGROUND: Hyperglycemia condition in diabetes mellitus (DM) influences proinflammatory cytokine levels and disrupts antioxidant balances. Glycated Hemoglobin is used as a biomarker of glycemic control in DM. AIM: This study aimed to analyse the association between glycated Hemoglobin with the levels of serum proinflammatory cytokines (interleukin (IL)-6) and antioxidants (glutathione peroxidase (GPx) and glutathione (GSH)) in type 2 diabetes mellitus (T2DM) patients in Universitas Sumatera Utara (USU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…It related to the secretion of prostaglandin by mesangial cells of kidney leading to changes in renal structure which are important in the development of DN [18]. In addition to this study ,Sari MI et alalsodetermined that serum IL-6 levels raised in patients with diabetic nephropathy [19]. Also a previous study has reported a significant difference in the IL-6 levels between a group of diabetic patients and a group of healthy people [20].…”
Section: Discussionsupporting
confidence: 50%
“…It related to the secretion of prostaglandin by mesangial cells of kidney leading to changes in renal structure which are important in the development of DN [18]. In addition to this study ,Sari MI et alalsodetermined that serum IL-6 levels raised in patients with diabetic nephropathy [19]. Also a previous study has reported a significant difference in the IL-6 levels between a group of diabetic patients and a group of healthy people [20].…”
Section: Discussionsupporting
confidence: 50%
“…The process continues to decrease antioxidants levels. Previous study showed that there was a decrease of glutathione peroxidase and glutathione in DM patients compared to healthy subjects [30]. The other study showed that decrease of SOD level occurred in tuberculosis patients with DM compared to healthy subjects [31].…”
Section: Discussionmentioning
confidence: 93%
“…Interleukin-6 (IL-6) is a pro-inflammatory cytokine that has been implicated in various conditions such as cardiovascular disease, diabetes mellitus, etc. 14,15,16 Circulating levels of IL-6 may be influenced by common genetic variants of the IL-6 gene promoter. Several IL-6 gene SNPs in the IL-6 promoter region have been identified, such as SNP rs1800797 (-597 G/A or -598 G/A).…”
Section: Resultsmentioning
confidence: 99%